Non-traumatic myositis ossificans - Nidhin Rehman; Harish Sadashiva; Manoj Gopal Madakshira; Deep Kumar Raman (University of São Paulo, 2021)
Myositis ossificans (MO) is a benign, ossifying lesion that usually affects the skeletal muscle. The rare non-traumatic form of MO can cause diagnostic dilemma and management issues. These lesions, however, have similar radiology and histopathological characteristics described in the more frequently encountered traumatic forms. Depending on the stage of the lesion, the inherent feature of myositis ossificans varies, and so does the management of the lesion. We describe a non-traumatic MO occurring in latissimus dorsi of a young girl and discuss the review of literature on this rare subtype.